Foraging potential of underground storage organ plants in the southern Cape, South Africa. Issue 101 (December 2016) - Singels, Elzanne; Potts, Alastair J.; Cowling, Richard M.; Marean, Curtis W.; De Vynck, Jan; Esler, Karen J.
Abstract: Underground storage organs (USOs) serve as a staple source of carbohydrates for many hunter-gatherer societies and they feature prominently in discussions of diets of early modern humans. While the way of life of hunter-gatherers in South Africa's Cape no longer exists, there is extensive ethnographic, historical, and archaeological evidence of hunter-gatherers' use of USOs. This is to be expected, given that the Cape supports the largest concentration of plant species with USOs globally. The southern Cape is the location of several Middle Stone Age sites that are highly significant to research on the origins of behaviourally modern humans, and this provided the context for our research. Here, we evaluate the foraging potential of USOs by identifying how abundant edible biomass is in the southern Cape, how easily it is gathered, and how nutritious it is. One hundred 5 × 5 m plots were assessed in terms of USO species and abundance. Nearly all of the sites sampled (83%) contained edible USOs and some had high concentrations of edible biomass. Extrapolating from these sites suggests that the edible USO biomass falls within the range of biomass observed in areas supporting extant hunter-gatherer communities. The nutritional content for six USO species was assessed; these contained between 40 and 228 calories/100 g. Furthermore, foraging events were staged to provide an indication of the potential return rates for the same six USOs. The target species grow near the soil surface, mostly in sandy soils, and were gathered with minimal effort. Some 50% of the foraging events conducted yielded enough calories to meet the daily requirements of a hunter-gatherer within two hours. In conclusion, we demonstrate that USOs are a readily available source of carbohydrates in the southern Cape landscape and, therefore, there is a strong possibility that USOs played a critical role in providing food for early humans.